The Musical Intelligence in kindergarten children (Journal of the College of Education for Women, 2019)
The childhood of the important stages in which the adopted child's personality, mental and physical, motor and configure , as well as gain experience , it is the basis on which the future life of the child , studies have unanimously competent in the fields of childhood verily the first five years of a child of the most important stages of life and the most fertile life . Because the stage Childhood its an active role as the foundation upon which to build human personality , it was necessary to create all leads to raise the level of intelligence of children , because intelligence is the first element in the organization of thinking makes the child able to do the activities characterized by mental qualities .Indicated most of the scientists, there is a mental and intellectual series deals with a number of intelligences , including musical intelligence , that music intelligence is thefoundation upon which to build the artistry capacity , because it is inspired by a sense of the individual environmental beauty, taste of nature and you pay to become more understanding to the content of the aesthetic elements of the environment , also, the family that develop musical intelligence of her child , help to gain a lot of different values and principles , including: respect for his homeland, and to respect the rights of others and the rights of the community in which he lives , working on widening the intellectual, linguistic, emotional and imaginary field when, for example, learned how to coordinate his voice to learn a particular skill or experience, and thus grow human being sound and integrated.Given the importance of music in a child intelligence kindergarten , and the lack of studies on this topic , the researcher sought to measure the musical intelligence of kindergarten children By building a test of intelligence musician at the age of (5-6) years based on the theory (Wing) musical intelligence, researcher chose Kindergarten (AL- Slam) of the Directorate of Baghdad / Karkh second in the AL-Alam area , and that the number of its children (187) boys and girls .In order to test the application for adoption , researcher Extracted transactions discrimination and difficulty of the paragraphs of the test , validity to the test as a whole transactions ,and its fields, the test includes the three areas, it is as follows: (Music cognition), which consists of (30) items , (musical taste), which consists of (3) items , and finally (Music Performance), which consists of (8) items , bringing the number of items of the test as a whole (41) items.After the test application on the research sample consisting of (187 ) children, the data were analyzed Which Obtained by researcher Children of answers on the test , and introduced the statistical system (SPSS) , results of the study revealed that the kindergarten children were suffering from the weakness of their intelligence in music, compared with the average premise, researcher This result was interpreted according to the theory (Wing) that the by relying in the search , that the cause of the weakness of children in kindergarten musical intelligence goes back to different musical productions on the three areas identified by (Wing) to his test.The researcher also provided after receiving a Search some of the recommendations and suggestions which it considered useful to researchers and the concerned authorities in this issue result.